E-COMMERCE PENJUALAN KOPI GAYO (Studi Kasus : UMKM Ine Kopi di Kecamatan Bandar) - Ilham Mabrur; Mahmuda Saputra; Hendry Syahputra (Universitas Gajah Putih, 2022)
E-Commerce is a flexible buying and selling system where a buyer does not need to come to a physical store to buy an item. Currently e-commerce is one of the alternative options for a business that is especially engaged in the field of processed coffee as a medium of information that facilitates interaction between sellers and buyers without limited space and time. Coffee is one of the leading commodities in plantation subsectors in Indonesia, especially in the gayo karana highland area because it has good market opportunities at home and abroad and also has an important role in the Indonesian economy, one of which is the Ine kupi business owned by individuals who are on the main shah road, bahgie bertona village, Kec Bandar, Bener Meriah, Aceh where with the design of this sales e-commerce system can make it easier for consumers to order products on Ine Kupi as long as they are connected to the internet network, Consumers only need to register, login and place an order.